Strategic Solutions for Women’s Empowerment through Islamic Social Finance in Light of Maqaŝid Sharia: A Delphi-ANP Approach - Widiastuti, Tika; Mawardi, Imron; Zulaikha, Siti; Ergun, Hüseyin; Abidin, Zainal (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
Women in Indonesia continue to face challenges in achieving economic and social independence. In fact, in Islamic law's framework, particularly Maqāṣid Syarī’ah's, Islamic Social Finance (ISF) emerges as a pivotal instrument for advancing women's empowerment. This study aims to identify key problems and strategic solutions for women's empowerment through Islamic social finance while predicting the future direction of empowerment itself. Utilizing the Delphi Analytical Network Process, this research conducted literature reviews, focus group discussions, and expert interviews across academia, practice, and regulatory bodies. The findings highlight critical problems from three dimensions for enhancing women's welfare: women's limited time since they have multiple roles (wife and mother) (0.116), capital provision from Islamic social finance institutions without assistance (0.200), and lack of shared information to muzakkī/donors on the importance of empowering women (0.315). Key strategic solutions include addressing essential needs prior to empowerment (0.054), customizing programs to recipients' interests (0.053), and providing financial literacy training (0.052). For Islamic social finance institutions, priorities include creating a comprehensive empowerment framework (0.137), fostering collaborations (0.128), and enhancing institutional capacities (0.115). Improving funding transparency (0.315) and channeling funds through institutions (0.221) are crucial in donor engagement.